Principles of accounting: tools for business decision making - Kimmel, Paul D.; Weygandt, Jerry J.; Kieso, Donald E. ([S.l.] : Wiley, 2004)
This book starts with a macro view of accounting information by presenting real financial statements. The authors establish how financial statements communicate the financing, operation, and investing activities of a business. To integrate the use of financial statements for decision-making, the authors identify a finite set of tools necessary to make business decisions based on financial information. The Decision Toolkit is provided for the reader and integrated throughout the text.
Keywords: accounts